2017
DOI: 10.1002/asia.201700129
|View full text |Cite
|
Sign up to set email alerts
|

Dipyrrin‐Bis(N‐Confused Porphyrin) Conjugate: Synthesis, Synergetic Ligation and Chirality Sensing

Abstract: A fully conjugated system 4 consisting of two 2-aza-21-carbaporphyrin (NCP) subunits bridged by dipyrrin was synthesized by a highly selective condensation of 3-pyrrole-NCP 2 with aryl aldehydes. The free base 4 as well as its silver(III) complex 5 exhibited flexibility of the bridge allowing synergetic binding of Ag , thus leading to a mixed-valence tetraporphyrinic assembly consisting of eight silver atoms which was characterized both in the solid state and in solution. Binding of chiral acid by 4 and 5 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…However, it was demonstrated that the capping [AgNO3(lut)] remained coordinated to the monomeric unit in solution. [46][47] at the α positions and have studied its assembly with silver salts [48]. Upon reaction with AgOAc, a neutral binuclear Ag(III) complex was obtained, [(13H)Ag2].…”
Section: Tris-pyrrolic Ligandmentioning
confidence: 99%
“…However, it was demonstrated that the capping [AgNO3(lut)] remained coordinated to the monomeric unit in solution. [46][47] at the α positions and have studied its assembly with silver salts [48]. Upon reaction with AgOAc, a neutral binuclear Ag(III) complex was obtained, [(13H)Ag2].…”
Section: Tris-pyrrolic Ligandmentioning
confidence: 99%
“…In all cases, the H1′ proton resonated at δ 0.5–0.6 ppm, and correlated with a signal at δ C 32 ppm in the 1 H, 13 C HSQC spectrum as well as with protons of the R 1 subsitutent in the 1 H, 1 H NOESY spectrum. The marked upfield shift of H1′ relative to the corresponding protons in quasi‐dipyrromethanes consisting of aromatic porphyrinoids ( δ ≈5 ppm) is suggested to originate from the paratropic shielding effect caused by the antiaromatic norcorrole rings. A similar shielding is observed for ortho protons of aromatic substituents R 1 whose signals are shifted to ca.…”
Section: Methodsmentioning
confidence: 99%
“…224 In acetylene-bridged NCP dimers, a unique interaction between two NCP moieties was observed. 225 226 The dimers 192 showed the guest-binding ability against enantiopure 10-camphorsulfonic acids, which could be detected by the CD spectra. Meanwhile, bipyrrole-bridged NCP dimer was synthesized by the metal-mediated coupling reaction of 20-pyrrolyl-NCP 193 (Scheme 71).…”
Section: Chemical Functionalizationmentioning
confidence: 99%
“…The acid-mediated reaction of NCP with pyrrole 35 gave 3-(2′-pyrrolyl)-NCP 191 in 66% yield (Scheme ). Subsequent condensation reactions of 191 with aryl aldehyde afforded the dipyrrin-bridged NCP dimers 192 in 53–71% yields . The dimers 192 showed the guest-binding ability against enantiopure 10-camphorsulfonic acids, which could be detected by the CD spectra.…”
Section: N-confused Porphyrinsmentioning
confidence: 99%